Comparing Medical Doctor's view on Alternative Medicine in Taiwan and Sweden: Comparing Medical Doctors' Views on Alternative Medicine - Fahad Baig, Mirza Muhamad (Pakistan Journal of Health Sciences, 2023)
Numerous research endeavors have delved into the perceptions of medical physicians regarding alternative medicine; nevertheless, none have employed the symbolic interaction paradigm to scrutinize their individual viewpoints. Objective: To broaden our knowledge of complementary medicine by analyzing the viewpoints and engagement with it among individuals hailing from Taiwan and Sweden. Methods: Semi-structured interviews were conducted with a diverse group of medical professionals from Taiwan and Sweden, representing a range of specialties and levels of experience. Results: Four themes were identified: (1) Evidence-based medicine, (2) The views of medical doctors on alternative medicine, (3) Belief associated with alternative medicine, and (4) Stigma associated with alternative medicine. Conclusions: The findings indicate a common understanding of Western medicine as evidence-based among both Taiwanese and Swedish doctors, with Taiwanese doctors also viewing alternative medicine as experience-based, reflecting the influence of local history, social context, and regulations.